Dataset for Benchmarking Time-Resolved Non-Line-of-Sight Imaging - Galindo Ramos, Miguel Jorge; Marco Murria, Julio; Gutiérrez Pérez, Diego; Jarabo Torrijos, Adrián (Jornada de Jóvenes Investigadores del I3A, 2019)
Time-resolved imaging has made it possible to look around corners by exploiting information from indirect light bounces. While there have been successive improvements in the field since its conception, so far it has only been proven to work in very simple and controlled scenarios. We present a public dataset of synthetic time-resolved Non-Line-of-Sight (NLOS) scenes with varied complexity aimed at benchmarking reconstructions. It includes scenes that are common in the real world but remain a challenge for NLOS reconstruction methods due to the ambiguous nature of higher-order diffuse bounces naturally occurring in them. With over 300 reconstructible scenes, the dataset contains an order of magnitude more scenes than what is available currently. The final objective of the dataset it to boost NLOS research to take it closer to its real-world applications.